Bond graph model of line-start permanent-magnet synchronous motors - Mahmoudi, Amin; Roshandel, Emad; Kahourzade, Solmaz; Vakilipoor Takaloo, Fardad; Drake, Samuel (Electrical Engineering, 2024)
The bond-graph (BG) enables to model multi-physics systems in the energy domains. This paper shows that BG models are an alternative, more intuitive and simpler to interpret, graphical tool as compared to existing dynamic models for performance prediction of the line-start permanent-magnet synchronous motors (LSPMSMs). It includes electrical, magnetic, and mechanical energy domains where the stator windings, rotor bars, and permanent magnets are the main components of the model. The dynamical equations of the proposed BG are extracted and solved using the MATLAB ordinary differential equation solver for a sample LSPMSM. The dynamics of the studied LSPMSM is investigated under two operating conditions (1) a healthy motor and (2) a motor with broken rotor bars. The simulation results are compared with the finite-element analysis (FEA) as the most accurate method to simulate the electric motor behaviour. It is shown that the proposed BG model accurately predicts the performance parameters of the motor such as current, torque, and speed under various operating conditions. In addition to the modelling validation, the transient behavior of the LSPMSM are discussed to describe the possible reasons for its behaviour during transient and steady-state operating conditions.
Created from Fastlane, Scopus look-up
Keywords: Bond graph; Dynamics model; Fault analysis; Line-start permanent-magnet synchronous motor; Squirrel cage; Transient analysis